Inequality in Southern Africa : An Assessment of the Southern African Customs Union - World Bank (Washington, DC, 2022)
The Southern African Customs Union (SACU) is the most unequal region in the world. While there has been some progress in recent years, inequality has remained almost stagnant in the most unequal countries. Using an innovative framework, this report provides a systematic and comprehensive analysis of inequality in the region. The main conclusions are as follows: first, inherited circumstances over which an individual has little or no control (i.e., inequality of opportunity) drive overall inequality, and their contribution has increased in recent years. This is an important concern particularly because this type of inequality is not the result of people’s efforts. Second, lack of access to jobs and means of production (education, skills, land, among others) by disadvantaged populations slows progress towards a more equitable income distribution. In a context where jobs are scarce, having post-secondary or tertiary education is key to both accessing jobs, and obtaining better wages once employed. Third, fiscal policy helps reduce inequality through the use of targeted transfers, social spending, and progressive taxation, but results are below expectation given the level of spending. Fourth, vulnerability to climate risks and economic shocks makes any gains towards a more equal society fragile. Looking ahead, accelerating inequality reduction will require concerted action in three policy areas: (a) expanding coverage and quality of education, health, and basic services across subregions and disadvantaged populations to reduce inequality of opportunity; (b) strengthening access to and availability of private sector jobs. It is important to accompany structural reforms with measures that facilitate entrepreneurship and skills acquisition of disadvantaged populations, and to improve land distribution and productivity in rural areas; and (c) investing in adaptive social protection systems to increase resilience to climate risks and economic vulnerability, while enhancing targeting of safety net programs for more efficient use of fiscal resources.